Application of Electrocoagulation for Wastewater Treatment of Tofu Production - Ino Eben Lasroha L.Toruan; Sirajudin Haji Abdullah; Sukmawaty Sukmawaty; Diah Ajeng Setiawati (Protech Biosystems Journal, 2021)
This study aims to process tofu wastewater by using the electrocoagulation method and determine TSS, TDS, and pH efficiency. The Electrocoagulation system was designed based on an electrocoagulation general standard called batch systems. This study used voltage variations of 10, 20, and 30 volts and exposure time during 60, 120, and 180 minutes. The parameters observed were Total Suspended Solid (TSS), Total Dissolved Solid (TDS), and acidity (pH). This study used fresh tofu wastewater with temperature 40-50oC, with a volume of 2000 ml wastewater in one time of electrocoagulation process. The results showed that the designed electrocoagulation system could reduce TSS concentration until 72.2% and TDS 15.4% and increasing pH approaching the neutral value. However, the concentration value of TSS and TDS  was still above the quality standard. Initial characteristics of tofu wastewater with pH 4.6, TSS 2396.4 mg/L, and TDS 2975.1 mg/L after electrocoagulation process gained pH values 6.5, TSS 1072.7 mg/L, and TDS 2621.6 mg/L.